Green Open Space System in an Effort to Increase Green Open Space in the Tangerang City Area - Eko Adhy Setiawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The first stage of this research was carried out in the city of Tangerang, especially in green open spaces, by analyzing green open spaces based on land use that has potential in the area as a green open space system. One of the landscape elements found in urban areas is urban parks, environmental parks, urban forests, river banks, railroad banks, green lanes, roads and so on. The problems that develop and exist are mainly in green open space planning, where the plan is made after a plan is finished, so that green open spaces are not integrated, and are not connected to various elements of the city area. So that achieving 30% green open space in urban areas is difficult, if implemented it will take a relatively long time. The City of Tangerang in terms of land area and green open space is still 15% and in terms of land use has not yet formed a continuous green open space system, so one green open space with other green open spaces still stands alone. The aim of the research is to map the existence of green open spaces in the city of Tangerang, so that an overview or profile of green open spaces is obtained, as the first stage of the research conducted. The research method was designed qualitatively with a case study approach.